CT screening for lung cancer: Is the evidence strong enough?. (January 2016) - Field, J.K.; Devaraj, A.; Duffy, S.W.; Baldwin, D.R.
Highlights: Do we have sufficient evidence to implement lung cancer CT screening? Focused on the level of readiness (red, amber, green) in twelve specific areas. Recruitment of the Hard to Reach is the only current red category. Mortality data, cost effectiveness, screen interval, smoking cessation are amber. Await the NELSON publication—in meantime we should be planning to implement. Abstract: The prevailing questions at this time in both the public mind and the clinical establishment is, do we have sufficient evidence to implement lung cancer Computed Tomography (CT) screening in Europe? If not, what is outstanding? This review addresses the twelve major areas, which are critical to any decision to implement CT screening and where we need to assess whether we have sufficient evidence to proceed to a recommendation for implementation in Europe. The readiness level of these twelve categories in 2015 have been with colour coded, where green indicates we have sufficient evidence, amber is borderline evidence and red requires further evidence. Recruitment from the 'Hard to Reach' community still remains at red, while mortality data, cost effectiveness and screening interval are all categorised as amber. The integration of smoking cessation into CT screening programmes is still considered to be category amber. The US Preventive Services Task Force have recommended that CT screening is implemented in the USA utilising the NLST criteria, apart from continuing screening to 80 years of age. The cost effectiveness of the NLST was calculated to be $81, 000/QALY, however, its well recognised that the costs of medical care in the USA, is far higher than that of Europe. Medicare have agreed to cover the cost of screening but have stipulated a number of stringent requirements for inclusion. To date we do not have good CT screening mortality data available in Europe and eagerly await the publication of the NELSON trial data in 2016 and then the pooled UKLS and NELSON data thereafter. However in the meantime we should start planning for implementation in Europe, especially in the areas of the radiological service provision and accreditation, as well as identifying novel mechanisms to recruit from the hardest to reach communities.